Pencabutan Hak Politik Pelaku Tindak Pidana Korupsi dalam Perspektif Hak Asasi Manusia - Dina Fajar Indah; Haris Retno Susmiyati; Rini Apriyani (Jurnal Risalah Hukum, 2020)
ABSTRACT The judge took the progressive step. This step strongly supports the prevention and eradication of Corruption Crimes. However, in implementing the revocation of rights, the time limit for revocation must be explicitly given for the right to vote. This study aims to find out additional crimes in the form of revocation of rights to choose and be elected to public office if reviewed from the perspective of criminal law and to find out the compatibility between the decisions of the Supreme Court judge Number 537K / Pid.Sus / 2014 with human rights principles. This study uses doctrinal types. Namely, the authors collect material from the literature. These are hardcopy and softcopy that relate to the title of this study and by using an analysis of the object of research. The results obtained from this study are as follows: 1). Revocation of the right to choose and be chosen should be based on the crime rate, the impact caused to society, and the position of the position while doing the crime of corruption. Revocation of certain rights must be determined by a judge’s decision, and there is a time limit for revocation according to what has been stipulated in article 38 Criminal Code. However, Article 38 of the Criminal Code does not regulate specifically related time constraints for the removal of the right to vote and elected in public office. 2). Revocation of the right to be elected in public office complies with the principles of human rights. It can be said to be included in the category of degradable rights, or rights can be restricted. While the revocation of the right to vote who are not given the time constraints and repeal incompatible with the principles of human rights. Because the right to vote is a fundamental right of every citizen, who has been guaranteed by the constitution of 1945, besides, the time limit for the removal of the right to vote still needed due to respect of human rights offender criminal acts of corruption but to provide justice for victims of crime over the extraordinary crime then the period of revocation may be given more long, judging from the level of crimes committed.Keywords: rights; Human Rights; Revocation; Criminal; Corruption